Efektifitas Penarikan Retribusi Parkir Pasar Ditinjau Dari Kualitas Pelayanan - Benny Andriawan (Universitas Islam Kadiri, 2020)
One of the main components of Regional Original Revenue is regional retribution. Thus in order to improve the ability of Regional Original Revenue, one of them can be achieved by increasing regional revenues from the regional retribution sector. The service quality received by market users as retribution payers will affect the achievement of market retribution targets. The thesis purpose was to analyze the effect of the service quality of Industry and Trade Departement on the effectiveness of withdrawing market parking retribution in Blitar City. The research design was intended to test the research hypothesis and to interpret the causal relationship between independent variables and dependent variables, namely the variable service quality of the market service (X) and the effectiveness of withdrawing market parking retribution (Y). The population was the people who use parking on the market of Blitar City which amounts to an average of 880 people every day. The sample size was 90 respondents with Proportionate Stratifeid Sampling technique. The research instrument used a questionnaire and has been tested for validity and reliability testing. To test or measure the effect of exogenous variables on the endogenous variable used rimple regression analysis. The results showed that there was an effect of the service quality of Industry and Trade Departement affected the effectiveness of withdrawing the parking market retribution in the city of Blitar. The t value was 20,859 that higher than t-table value amount 1,980. The coefficient of determination between the service quality variable of the Trade and Industry Departement (X) with the variable effectiveness of the withdrawal of the market parking retribution (Y) is (0.912)2 = 0.832. This figure indicates that there was 83,2% changes to variable Y explained or determined by variable X. Based on the results, it is expected that the Trade and Industry Departement had improve the quality and quantity of market facilities and infrastructure and parking, so that traders can run their business maximally and consumers are comfortable to shop in traditional markets.